The Role of Enterprise Agility in Mediating Digitalization Capabilities Towards Superior Performance of MSMEs - Purnama, Muzzamil Putra; Isfianadewi, Dessy (MEC-J (Management and Economics Journal), 2024)
Many companies have launched new models of digital technology support during the COVID-19 pandemic, such as online sales, digital customer interaction, online employee training, and remote workforce solutions, not all companies have benefited. Covid-19 has enough impact on the economy to make business people inevitably have the ability to adjust their agility skills so that their business can survive in the new normal era. This research aims to analyze the influence of digitalization capabilities, mediated by market utilization agility and operational adjustment agility, on the performance of MSMEs in Sleman, Special Region of Yogyakarta. This research uses a quantitative approach, the population to be studied is Sleman MSMEs that have digitalization capabilities, this research uses Purposive Sampling technique, A total of 105 MSME respondents in Sleman, Yogyakarta, filled out a questionnaire, which was analyzed using SmartPLS 3. The research results indicate that digitalization capabilities have a positive impact on market utilization agility and operational adjustment agility. Market utilization agility does not have a significant effect on the performance of MSME companies. Operational adjustment agility has a positive impact on the performance of MSME companies. The capability of digitalization does not have a significant impact on the performance of MSME companies. The study finds that market utilization agility does not serve as a mediator between digitalization capabilities and MSME performance. Instead, operational adjustment agility fully mediates this relationship, highlighting its critical role. These findings provide valuable insights for MSME practitioners in understanding the interplay between digitalization capabilities, market utilization agility, operational adjustment agility, and their collective influence on company performance